The next generation of strength and conditioning practice to enhance performance and reduce injury risk: virtual reality-based integration of neuromuscular, neurocognitive, and sensorimotor training - McPherson, A. L.; Hogg, J. A.; Foreman, E.; Riehm, C. D.; Howell, D. R.; Grooms, D. R.; Myer, G. D. (Strength and Conditioning Journal, 2025)
Sport-related concussion (SRC) increases the risk of subsequent lower extremity musculoskeletal injury, particularly in youth athletes. This may be due to SRC-altered movement patterns, particularly under neurocognitive challenges. Specifically, dual-tasking—simultaneously completing motor and cognitive tasks—can distinguish patients with a higher risk of lower extremity musculoskeletal injury, offering a unique and unexplored intervention target for clinical, rehabilitation, strength and conditioning practitioners, and coaches. This narrative provides evidence outlining the addition of cognitive components to movement-based interventions to reduce injury risk after SRC. We propose a theoretical framework for a virtual reality-based neuromuscular training intervention that incorporates dual-tasking to target deficits underlying potential mechanisms of increased injury risk after SRC. Virtual reality technology offers a unique environment that may help reduce lower extremity musculoskeletal injury risk after SRC to improve long-term health, well-being, and athletic performance.